KEGIATAN MICROTEACHING TENTANG NUMERASI DASAR DI SD NEGERI 195 BENGKULU UTARA - Putri, Milladina (TRIBUTE: JOURNAL OF COMMUNITY SERVICES, 2024)
The individual KKN work program, entitled "Microteaching Activities About Basic Numeracy at SD Negeri 195 North Bengkulu" is an activity carried out to increase students' understanding of SD Negeri 195 Bengkulu Utara, especially grade 4 SD regarding basic numeracy. This activity is expected to provide students with an understanding of learning numeracy. The main goal that has been achieved through this KKN activity is the creation of regular and fun learning activities. In addition, it was also found that grade 4 students' understanding of learning was quite good.